Corporate Social Responsibility and Shipping Views of Baltic Sea Shipping Companies on the Benefits of Responsibility - Kunnaala, Vappu; Rasi, Mirja; Storgård, Jenni (Publications of the Centre For Maritime Studies, University of Turku, A 70, 2013)
The safety of shipping operations in the Baltic Sea is an extensively studied issue due to the density of traffic and the ecological sensitivity of the area. The focus has, however, mainly been on ship technology or on traffic control measures and the operative safety aspect of shipping is in a minor position in maritime safety studies and is lacking in terms of solutions. Self-regulatory and voluntary measures could be effective ways to improve the operational safety of shipping. Corporate social responsibility, or CSR, is one example of a voluntary measure that the shipping companies can take. CSR can enhance maritime safety and improve the shipping companies’ competitiveness. The aim of this study is to increase the knowledge of CSR in the maritime sector and study its applicability and benefits to the shipping companies. The research comprises of a theory part and a questionnaire study, which examine the significance of corporate social responsibility in shipping companies’ maritime safety and competitiveness. The aim of the questionnaire study is to find out how corporate social responsibility is implemented in the shipping companies. According to the literature review, responsible actions can produce financial and time costs, but due to these actions cost savings in the form of learning and increased efficiency can be achieved. Responsible actions can also produce concrete improvements and a reputation of responsibility that can lead to both cost savings and increase in the company’s income. CSR is recognised as having real business benefits in terms of attracting customers and high-quality employees. In shipping, CSR usually focuses on environmental issues. Environmental social responsibility in shipping is mainly motivated by the need to comply with existing and forthcoming regulation. Shipping companies engage in CSR to gain competitive advantage and to increase maritime safety. The social aspects of CSR take into account the well-being and skills of the employees, corporation and other stakeholders of the company. The questionnaire study revealed that the most common CSR measures in shipping companies are environmental measures, and that environmental concerns are considered to be the most important reason to engage in CSR. From the preliminary question about the concept of CSR it can also be seen that safety issues are commonly considered to be a part of CSR and safety gains are the second most important reason to engage in CSR. From the questionnaire, it can also be extrapolated that gaining a better reputation is one of the most important reasons to engage in CSR in the first place. For example, the main economic benefit was seen to be the increase of customer numbers as a result of a better reputation. Based on the study, it would seem that companies are starting to realise that they might gain competitive advantage and be favoured as shippers if they engage in sustainable, responsible operations and present themselves as “green”.

Merenkulun turvallisuutta Itämerellä on tutkittu laajasti alueen suurten liikennemäärien ja ympäristön haavoittuvuuden vuoksi. Tutkimuksen pääpaino on kuitenkin ollut lähinnä alusten teknisissä ratkaisuissa tai liikenteen ohjauksessa, jolloin operatiivisen turvallisuuden osa-alueet ovat jääneet vähemmälle huomiolle ja siihen liittyvät ongelmat ovat yhä suurilta osin ratkaisematta. Itsesääntely ja muut vapaaehtoiset toimenpiteet voisivat olla tehokas keino parantaa merenkulun operatiivista turvallisuutta. Vastuullinen liiketoiminta on yksi esimerkki vapaaehtoisista toimista, joita voidaan toteuttaa merenkulkualalla. Vastuullinen liiketoiminta on keino parantaa merenkulun turvallisuutta sekä varustamoyritysten kilpailukykyä. Tämän tutkimuksen tarkoituksena on lisätä tietoisuutta yhteiskuntavastuullisesta liiketoiminnasta merenkulkualalla sekä selvittää, miten vastuullisuutta sovelletaan merenkulussa ja mitkä seikat motivoivat varustamoita toimimaan vastuullisesti. Tutkimus koostuu teoriaosuudesta ja kyselytutkimuksesta, jotka käsittelevät vastuullisuuden vaikutuksia varustamoyritysten kilpailukykyyn ja merenkulun turvallisuuteen. Kyselytutkimuksen tarkoituksena on selvittää, millä tavoin vastuullista liiketoimintaa sovelletaan merenkulkualalla. Kirjallisuuskatsauksen mukaan vastuullisuus voi tuoda yrityksille rahallisia ja ajallisia kustannuksia, mutta vastuullinen toiminta voi tuoda myös kustannussäästöjä esimerkiksi oppimisen ja toiminnan tehostumisen myötä. Vastuullinen liiketoiminta voi myös tuottaa konkreettisia parannuksia ja kohentaa yrityksen mainetta, mikä voi johtaa sekä kustannussäästöihin että lisätä yrityksen tuloja. Vastuullisuus voi myös houkutella lisää asiakkaita ja ammattitaitoisia työntekijöitä. Merenkulkualalla vastuullisuus liittyy usein ympäristöön. Ympäristövastuun pääpainona merenkulussa on usein pyrkimys noudattaa nykyisiä ja tulevia ympäristösäännöksiä. Varustamoyritykset toteuttavat vastuullista liiketoimintaa saavuttaakseen kilpailuetua ja parantaakseen merenkulun turvallisuutta. Sosiaalisen vastuun alalla varustamot ottavat huomioon työntekijöiden hyvinvoinnin ja osaamisen sekä yrityksen eri sidosryhmät ja niiden vaatimukset. Kyselytutkimuksen perusteella vastuullisuuteen liittyvät toimenpiteet liittyvät useimmiten ympäristöön ja ympäristöseikat ovat tärkein syy toimia vastuullisesti. Vastuullisen liiketoiminnan käsitettä koskevaan kysymykseen annettujen vastausten perusteella voidaan sanoa, että turvallisuutta pidetään yleisesti olennaisena osana vastuullista liiketoimintaa. Lisäksi turvallisuuden edistämistä pidettiin toiseksi tärkeimpänä syynä toteuttaa vastuullista liiketoimintaa. Tuloksista voidaan myös päätellä, että paremman maineen saavuttaminen on yksi olennaisimmista syistä toimia yhteiskuntavastuullisesti. Tärkeimpänä vastuullisuuden taloudellisena hyötynä pidettiin hyvästä yritysmaineesta johtuvaa asiakasmäärän kasvua. Tutkimuksen perusteella voidaan havaita, että varustamot ovat havainneet voivansa saavuttaa kilpailuetua toimimalla vastuullisesti ja olla suositumpi vaihtoehto varustamoiden joukossa, mikäli ne toimivat kestävän kehityksen mukaisesti ja tuovat itsensä esille vastuullisena ja ”vihreänä” varustamoyrityksenä.